Wafer fabrication : automated material handling systems - Zhang, Jie, 1963 September 21- (Walter de Gruyter GmbH, 2018)
This book systematically introduces modeling, performance evaluation and applications of Automatic Materiel Handling System (AMHS) in semiconductor manufactucing, and focuses discussion on the coordination of two subsystems. Resources dispatch and optimization are conducted on operational research combined with cases studies. Written in a practical way, it is an essential reference for researchers and engineers in manufacturing and management.